Back Cover: Enzyme‐Catalyzed Carbonyl Olefination by the E. coli Protein YfeX in the Absence of Phosphines (ChemCatChem 9/2016). Issue 9 (9th May 2016) - Weissenborn, Martin J.; Löw, Sebastian A.; Borlinghaus, Niels; Kuhn, Miriam; Kummer, Stefanie; Rami, Fabian; Plietker, Bernd; Hauer, Bernhard
Abstract : The Cover shows an enzymatic carbonyl olefination reaction in E.coli where the corresponding enzyme—depicted as the clownfish nemo—has to be found in the organism which is represented by the ocean. In their paper, Weissenborn, Löw et al. present a method to find new enzyme activities by utilizing an entire cell lysate with its thousands of proteins as catalyst. Once they found that the cell lysate catalyzes a carbonyl olefination reaction they determined, isolated, and studied the corresponding protein. The results show the first enzymatic carbonyl olefination in absence of phosphines, as well as the feasibility of the performed general approach in cell lysates. More information can be found in the Communication by Weissenborn, Löw et al. onpage 1636 in Issue 9, 2016 (DOI:10.1002/cctc.201600227 ).